Exploring the cardioprotective effect of synthetic wine in Long Evans rats - Dlamini, Lindizwe (Department of Medicine, 2015)
[No copyright notice] Background: Moderate and chronic consumption of red wine protects against cardiovascular disease. Wine is a complex matrix containing multiple molecules whose concentrations can vary from one bottle to another. Therefore, the delineation of the putative cardioprotective components in wine such as alcohol, resveratrol and melatonin is very challenging when using commercially available red wine. Aim: We aimed to use synthetic wine, whose composition is well characterized, to explore whether the presence of alcohol, resveratrol and melatonin (as found in commercial wines) contributes to the cardioprotective effect of chronic and moderate consumption of red wine (equivalent to 2 glasses of wine/day) in an animal model. Additionally, we hypothesized that synthetic wine enriched with resveratrol and melatonin confers cardioprotection via improvement of overall antioxidant profile.